Engineered nanomaterial interactions with bilayer lipid membranes: screening platforms to assess nanoparticle toxicity. (1st January 2013) - Negoda, Alexander; Liu, Ying; Hou, Wen-Che; Corredor, Charlie; Moghadam, Babak Yaghoubi; Musolff, Corey; Li, Lin; Walker, William; Westerhoff, Paul; Mason, Andrew J.; Duxbury, Phillip; Posner, Jonathan D.; et al.
Engineered nanomaterials (ENMs) have attractive functional properties and are increasingly being used in commercial products. However, ENMs present health risks that are poorly understood and difficult to assess. Because ENMs must interface with cell membranes to cause biological effects, improved methods are needed to measure ENM-biomembrane interactions. The goals of this paper are to review the current status of methods to characterise interactions between ENMs and bilayer lipid membranes that mimic cell membranes, and to present example applications of the methods relevant to nanotoxicology. Four approaches are discussed: electrochemical methods that measure ENM-induced ion leakage through lipid bilayers, optical methods that measure dye leakage from liposomes, partitioning methods that measure ENM distribution coefficients between aqueous solution and immobilised lipid bilayers, and theoretical models capable of predicting fundamental molecular interactions between ENMs and biomembranes. For each approach, current literature is summarised, recent results are given, and future prospects are analysed, including the potential to be used in a high-throughput mode. The relative advantages of the various approaches are discussed, along with their synergistic potential to provide multi-dimensional characterisation of ENM-biomembrane interactions for robust health risk assessment algorithms.